D4.1 ECoE Human Resources Framework and Policy - Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Nisantzi, Argyro; Michaelides, Silas; Anayiotos, Andreas; Neocleous, Kyriacos; Schreier, Gunter; Komodromos, Georgios; Tziortzis, Stelios (My University, 2020)
The aim of this report is to provide a sound policy for human resource acquisition and management for the Eratosthenes Centre of Excellence (ECoE). The report provides the overall human resources framework and policy for the ECoE. In addition, it includes the policies on diversity and gender equality, based on European and Cyprus law, as well as the policies of the ECoE. The operation of the ECoE will act as a hub to attract high-quality research personnel, limit the “brain drain” in the field and create appropriate conditions for a sustainable future regarding human resources. HR policies provide the necessary guidelines and policies for the ECoE to function in a smooth and efficient manner. In addition, it defines the necessary management standards necessary for making decisions on various organizational as well as personal issues. HR also documents all organizational policies and procedures, rules, regulations, etc. and communicates them to the employees. Lastly, it protects the legal interest of the ECoE as well as define the legal obligations of the employees towards the ECoE.
T4.1 Definition of Human Resources Framework and Policy
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Human Resources; Earth Observation; WP4